Absolute Tauberian Constants for H-J Hausdorff Matrices - Akgun, F. Aydin; Rhoades, B. E. (AMER INST PHYSICS, 2012)
We obtain absolute Tauberian constants for the H-J generalized Hausdorff transformations. As corollaries we obtain the analogous results for the E-J generalized Hausdorff matrices, and the results of Sherif for regular Hausdorff matrices.
Keywords: Tauberian constants; generalized Hausdorff matrices; Mathematics; Physics